Revisiting sustainable tourism in the Philippines : towards a better normal - Rivera, John Paolo R.; Gutierrez, Eylla Laire M.; Roxas, Fernando Martin Y. (New perspectives in tourism and hospitality management, 2024)
Revisiting Sustainable Tourism in the Philippines provides a comprehensive investigation into how sustainability across tourism industries can be achieved in practical terms within the Asian context. Existing books have tackled theories and principles of sustainable tourism, or have focused on practices and examples. This book combines both approaches by bridging the theoretical and practical aspects of pursuing sustainability in tourism industries. It serves as a guidebook and reference material for tourism practitioners, policymakers as well as members of the academe. Authors Rivera, Gutierrez, and Roxas have worked closely with government officials and national tourism agencies in implementing capacity-building workshops and developed research in relation to sustainable tourism. Their practical experience and theoretical knowledge is invaluable to anyone working in the field of sustainable tourism.